Effect Of Kenaf To Glass Fiber Ratio On The Properties Of Hybrid Pultruded Composite - Loh, Wai Cheong (Universiti Sains Malaysia, 2017)
The objective of this project was to investigate and determine the effect of kenaf to glass fiber ratio on the properties of hybrid pultruded composite. Before the production of samples, glass fibers and kenaf fibers were tested with miniature tensile machine to verify its diameter and single fiber tensile strength. The continuous glass and kenaf fiber rovings were used to reinforced with unsaturated polyester resin to produce rod shape samples with 12 mm diameter. The samples produced were hybrid PKGRC samples with 33, 47, 51 and 62 vol% and compared with a commercial PKRC sample. Compression and flexural test was used to determine the best combination of kenaf fiber and glass fiber yarn that will give the highest mechanical strength. Besides, a water absorption test was done to study the effect of aging on the compressive strength of each samples. Moreover, TGA was carried out to study the thermal stability of hybrid composite after glass fibers were added, a positive result has been obtained as the degradation temperature had been increase for the PKGRC sample. From the compression and flexural test, PKGRC sample with 47 vol% acquired the highest compression and flexural strength before and after aging. In addition, the result of water absorption test shows that the weight gain is closely related to the fibers reinforcement volume percent and arrangement of glass fibers to the kenaf fibers.